Effect of deep oscillation as a recovery method after fatiguing soccer training: A randomized cross-over study - Simon von Stengel; Marc Teschler; Anja Weissenfels; Sebastian Willert; Wolfgang Kemmler (Journal of Exercise Science & Fitness, 2018)
Background/Objective: In soccer the recovery time between matches is often not long enough for complete restoration. Insufficient recovery can result in reduced performance and a higher risk of injuries. The purpose of this study was to evaluate the potential of Deep Oscillation (DO) as a recovery method. Methods: In a randomized crossover study including 8 male soccer players (22 ± 3.3 years) the following parameters were evaluated directly before and 48 h after a fatiguing soccer-specific exercise: Maximum isokinetic strength of the leg and hip extensors and flexors (Con-Trex® Leg Press, Physiomed, Germany), rating of perceived exertion (RPE) during isokinetic testing (Borg scale 6–20), creatine kinase (CK) serum levels and Delayed Onset Muscle Soreness (DOMS; visual analogue scale 1–10). By random allocation, half of the group performed a DO self-treatment twice daily (4 applications of 15min each), whilst the other half received no intervention. 4 weeks later a cross-over was conducted. Two-way repeated measures analysis of variance was used to compare treatment versus control. Results: A significant treatment effect was observed for maximum leg flexion strength (p = 0.03; DO: 125 ± 206 N vs. CG: −115 ± 194; p = 0.03) and for RPE (DO: −0.13 ± 0.64; vs. CG: +1.13 ± 1.36; p = 0.03). There was a trend to better recovery for maximum leg extension strength (DO: −31 ± 165 N vs. CG: −138 ± 212; p = 0.028), CK values (DO: 72 ± 331 U/ml vs. CG: 535 ± 797 U/ml; p = 0.15) and DOMS (DO: 3.4 ± 1.5 vs. CG: 4.1 ± 2.6; p = 0.49). Conclusion: In the present study we found significant effects of DO on maximum leg flexion strength and perceived rate of exertion. Other variables showed a consistent trend in favour of DO compared with the control without significance. DO seems to be a promising method to accelerate the time-course of peripheral recovery of muscle which should be addressed in larger studies in future. Trial registration: ClinicalTrials.gov; NCT03411278, 18.01.2018 (during the study). Keywords: Soccer, Football, Regeneration, Deep oscillation, Electrical therapy